Pengukuran Kualitas Udara Particulat Matter ( PM2,5) Dalam Ruangan Di PT. Rekind Daya Mamuju - Farhan, Muhammad; Islam, Fahrul; Chairani H, Miftah (Jurnal Kesehatan Lingkungan Mapaccing, 2025)
According to the National Institute of Occupational Safety and Health (NIOSH), there are several sources of indoor pollution, one of which is pollution that comes from outside the building, for example chimney gas. PT Rekind Daya Mamuju is a company engaged in the Steam Power Plant (PLTU) business, in its production process using coal to produce steam. Burning coal in the production process produces smoke which is thought to contain PM2.5 which can fly into employees' work spaces.This research aims to measure and analyze the concentration of Particulate Matter (PM2.5), measure humidity levels, measure lighting, measure temperature levels, measure ventilation. Measurements were carried out at several points in the PT industrial room. Rekind Daya Mamuju over a certain period of time to get representative data. This research method is descriptive research with a cross-sectional design based on measuring indoor air samples.The results of the study showed that the concentration of PM2.5 in one room was above the standard threshold for PM2.5 quality standards in the room, namely the DCS room with a PM2.5 level of 71.3 Âµg/m3, the humidity level in the room that did not meet the requirements was the workshop room with humidity content 64%. , the temperature level in the room of 26.80C meets the requirements, the room whose ventilation does not meet the requirements is the workshop room. Conclusion: Average levels of PM2.5, humidity, temperature, ventilation have met the requirements. This research suggests implementing mitigation measures, such as improving ventilation, use of personal protective equipment, and reducing particulate emission sources, to reduce exposure to PM2.5 in industrial spaces.